2015
DOI: 10.1002/celc.201402436
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Electrooxidation in Bimetallic Suspensions of Nanoparticles in Alkaline Media

Abstract: Glucose electrooxidation at a glassy carbon rotating disk electrode in an alkaline bimetallic suspension of Au and Pt nanoparticles is studied. The voltammetric current density is approximately fourfold larger than measured for Pt nanoparticles in suspension and three orders of magnitude larger than observed for a suspension of Au nanoparticles. The features of these voltammograms are classically different from voltammograms obtained for suspensions of Au or Pt nanoparticles under the same conditions. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In turn, all component of the alloy catalysts can affect the activity enhancement [ 33 ]. Moreover, not only the electrocatalytic activity, but also the stability of bimetallic and trimetallic noble metal nanocrystals (NCs) are higher than those of their monometallic counterparts due to the modification of their electronic structures, available catalytically active sites and other positive synergistic effects caused by structural and compositional differences between the monometallic and bimetallic NCs [ 34 , 35 , 36 ]. However, the mechanisms that lead to a synergistic effect and an increase of catalytic activity towards glucose electrooxidation are quite complex and individual for each composite; therefore, in order to clarify such mechanism for the material synthesized in this work the separate study is required.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, all component of the alloy catalysts can affect the activity enhancement [ 33 ]. Moreover, not only the electrocatalytic activity, but also the stability of bimetallic and trimetallic noble metal nanocrystals (NCs) are higher than those of their monometallic counterparts due to the modification of their electronic structures, available catalytically active sites and other positive synergistic effects caused by structural and compositional differences between the monometallic and bimetallic NCs [ 34 , 35 , 36 ]. However, the mechanisms that lead to a synergistic effect and an increase of catalytic activity towards glucose electrooxidation are quite complex and individual for each composite; therefore, in order to clarify such mechanism for the material synthesized in this work the separate study is required.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the recorded parameters for laser-synthesize Pd50Au50 nanoalloys, including a low onset potential (< 0.27 V vs. RHE) and kinetics at lower potentials, accompanied by an impressive activity in the entire potential window, outperform all reported data for alternative bimetallic nanomaterials. [43][44][45][46][47] Fig. S2 of the Supplementary information shows a comparison of electrocatalytic performances of Pd50Au50 electrodes formed by laser-ablated NPs and NPs prepared by Bromide Anion Exchange based method recorded in 0.1 M NaOH at 20 mV s −1 and 20 °C in the presence of 10 mM glucose.…”
Section: Electrocatalytic Activities Towards Glucose Electrooxidationmentioning
confidence: 99%
“…Indeed, it was found that bimetallic catalytic micro-or nanostructures based on Pt are favorable due to the presence of a second metal atom that can synergistically facilitate catalytic activity and stability via electronic, alloying, or strain effects and availability of a greater number of catalytically active sites. 27,32 Possible reactions involved in the process of the electrooxidation of glucose under alkaline conditions on the surfaces of Ni electrodes modified with Au and Pt can be shown as follows: 9,10,42…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As an option, it can be done by increasing the surface area of the electrode material through its modification with nanosized structures. In general, this modification can be carried out, for example, by nanoparticles of precious metals, e.g., gold and platinum, chemically synthesized or obtained by photochemical reduction of their complexes. Indeed, implementation of the unique properties of three-dimensional structures with a large surface area of such catalytically active and biologically compatible metals as gold and platinum may significantly reduce analysis time and enhance the electrocatalytic activity of an enzyme-free electrode with respect to glucose sensing. , Alternatively, a similar effect can be achieved using electrode materials based on bi- or polymetallic structures manufactured by co-deposition of two or several metals upon laser irradiation. , …”
Section: Introductionmentioning
confidence: 99%